Ambivalence in the Woods: Baltimore Resident Perceptions of Local Forest Patches. Issue 7 (2nd July 2020) - Sonti, Nancy Falxa
Abstract: Wild urban forests may elicit positive and negative emotions, both at a community level and within an individual. This paper examines resident perceptions and use of local forest patches in Baltimore, Maryland across four case study neighborhoods selected for differences in homeownership and forest patch management. Semi-structured interview data reveal residents' strongly ambivalent attitudes toward urban wilderness across all study sites with only nuanced differences in perceptions based on homeownership and management regime. Baltimore residents living adjacent to forest patches were found to experience some of the restorative benefits associated with immersion in wild nature, even when they do not actually enter the woods. Positive experiences were balanced by negative emotions resulting from the perception that urban wilderness is chaotic and unpredictable. These ambivalent feelings may influence the benefits derived from these urban green spaces, as well as local residents' desires for their future structure and function as social-ecological spaces.